Navigating the new normal: Challenges in lecturers’ adaptation to online learning at a South African university of technology post-emergency remote teaching - Kaeane, Naledi Lenny; Molokomme, Radiakga Thabang (Edelweiss Applied Science and Technology, 2025)
Navigating the rapid shift from emergency remote teaching (ERT) to online learning has been one of the most transformative challenges higher education institutions face worldwide. As the COVID-19 pandemic forced higher education institutions (HEIs) to adopt digital platforms overnight, lecturers grappled with unforeseen obstacles in a rapidly changing academic landscape. The transition from ERT to sustainable online learning has posed significant challenges for HEIs globally. This study examines lecturers’ experiences at the University of Technology (UoT) in Gauteng, South Africa, following this shift in the post-COVID-19 era. The research aims to identify key challenges and institutional responses to online learning adaptation specifically after the shift from ERT. Using a qualitative case study approach, semi-structured interviews were conducted with twelve conveniently selected lecturers to explore their lived experiences. The study reveals persistent barriers such as inadequate digital infrastructure, insufficient lecturer training, and disparities in student access to resources. Lecturers also faced difficulties in maintaining student engagement, addressing digital literacy gaps, and navigating the absence of comprehensive support structures. Despite these challenges, institutions demonstrated resilience by implementing adaptive strategies to improve online learning delivery. While online learning offers opportunities for flexibility and innovation, addressing systemic shortcomings is crucial for long-term effectiveness. The study recommends investing in digital infrastructure, enhancing professional development for lecturers, and establishing tailored student support services. Future research should explore the long-term academic and psychological effects of online education and the role of emerging technologies in enhancing learning experiences.